GvmR – A Novel LysR-Type Transcriptional Regulator Involved in Virulence and Primary and Secondary Metabolism of Burkholderia pseudomallei - Duong, Linh Tuan; Schwarz, Sandra; Gross, Harald; Breitbach, Katrin; Hochgräfe, Falko; Mostertz, Jörg; Eske-Pogodda, Kristin; Wagner, Gabriel E.; Steinmetz, Ivo; Kohler, Christian (Frontiers in Microbiology, 2018)
Burkholderia pseudomallei is a soil-dwelling bacterium able to survive not only under adverse environmental conditions, but also within various hosts which can lead to the disease melioidosis. The capability of B. pseudomallei to adapt to environmental changes is facilitated by the large number of regulatory proteins encoded by its genome. Among them are more than 60 uncharacterized LysR-type regulators (LTTRs). Here we analyzed a B. pseudomallei mutant harboring a transposon in the gene BPSL0117 annotated as a LTTR, which we named gvmR (globally acting virulence and metabolism regulator). The gvmR mutant displayed a growth defect in minimal medium and macrophages in comparison with the wild type. Moreover, disruption of gvmR rendered B. pseudomallei avirulent in mice indicating a critical role of GvmR in infection. These defects of the mutant were rescued by ectopic expression of gvmR. To identify genes whose expression is modulated by GvmR, global transcriptome analysis of the B. pseudomallei wild type and gvmR mutant was performed using whole genome tiling microarrays. Transcript levels of 190 genes were up- and 141 genes were downregulated in the gvmR mutant relative to the wild type. Among the most downregulated genes in the gvmR mutant were important virulence factor genes (T3SS3, T6SS1 and T6SS2), which could explain the virulence defect of the gvmR mutant. In addition, expression of genes related to amino acid synthesis, glyoxylate shunt, iron-sulfur cluster assembly and syrbactin metabolism (secondary metabolite) was decreased in the mutant. On the other hand, inactivation of GvmR increased expression of genes involved in pyruvate metabolism, ATP synthesis, malleobactin and porin genes. Quantitative RT-PCR verified the differential expression of 27 selected genes. In summary, our data show that GvmR acts as an activating and repressing global regulator that is required to coordinate expression of a diverse set of metabolic and virulence genes essential for the survival in the animal host and under nutrient limitation.